Techno-economic analysis of geothermal green hydrogen: Investment validation through green accounting framework - Fitra Reza Fadhilah (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Indonesia faces a significant economic dilemma in aligning its growth targets with the 2060 net-zero emission (NZE) commitment, particularly within the geothermal sector which holds immense potential yet suffers from an investment paradox due to perceived high risks. While the geological reserves are abundant, the translation into bankable energy projects remains sluggish. This study aims to bridge this gap by validating the financial viability of geothermal-based green hydrogen production through a standardized techno-economic framework integrated with green accounting principles. Methods: The research proposes a hybrid Aakaline water electrolysis and solid oxide electrolysis cell (AWE-SOEC) system to maximize efficiency from stable geothermal baseloads. The methodology employs a rigorous techno-economic analysis (TEA) and a Monte Carlo simulation with 10,000 iterations to quantify investment risks and internalize environmental externalities such as carbon credits and oxygen by-products valuation. Findings: The findings demonstrate a highly competitive levelized cost of hydrogen (LCOH) at a median of 4.77 per kg. Furthermore, the project projects a net present value (NPV) of US95.1 million with an intiernal rate of return (IRR) of 49.6% along with a rapid payback period of 3.1 years that far exceeds standard industry hurdle rates. The stochastic analysis reveals a 98.2% probability of positive returns. Conclusion: Integrating green accounting metrics transforms the economic calculation from simple cost analysis into a comprehensive investment validation. The study proves that geothermal hydrogen is not only technically feasible due to thermal integration but also presents a premium profitability profile, suggesting that environmental compliance can be leveraged as a value driver for accelerating Indonesia's energy transition. Novelty/Originality of this article: This study integrates a techno-economic analysis, incorporating a novel AWE-SOEC hybrid electrolyzer configuration and a 10,000-iteration Monte Carlo simulation that internalizes environmental externalities, to produce the first probabilistic investment validation framework for geothermal-based green hydrogen in Indonesia.